Direct laboratory observation of velocity-saturation relation transition during rocks saturation - Lebedev, Maxim; Gurevich, Boris; Toms, J.; Clennel, B.; Pervukhina, Marina; Mueller, T. (2018)
Copyright © (2008) by the Society of Exploration Geophysicists All rights reserved. Ultrasonic velocities and fluid saturations are measured simultaneously during water injection into sandstone core samples. The experimental results obtained on low-permeability samples show that at low saturation values the velocity-saturation dependence can be described by the Gassmann-Wood relationship. However, with increasing saturation a sharp increase of P-wave velocity is observed, eventually approaching the Gassmann-Hill relationship. We relate this transition behavior to the change of the fluid distribution characteristics inferred from CT scans. In particular, we show that for relatively large fluid injection rate this transition occurs at smaller degrees of saturation as compared with high injection rate.